2017
DOI: 10.1589/jpts.29.224
|View full text |Cite
|
Sign up to set email alerts
|

Immediate effects of Graston Technique on hamstring muscle extensibility and pain intensity in patients with nonspecific low back pain

Abstract: [Purpose] The purpose of this study was to analyze the effect of Graston Technique on hamstring extensibility and pain intensity in patients with nonspecific low back pain. [Subjects and Methods] Twenty-four patients with nonspecific low back pain (27–46 years of age) enrolled in the study. All participants were randomly assigned to one of two groups: Graston technique group (n=12) and a static stretching group (n=12). The Graston Technique was used on the hamstring muscles of the experimental group, while the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
28
0
12

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 17 publications
4
28
0
12
Order By: Relevance
“…The Graton Technique and cervical Chuna manual therapy were done every two to three days for a total of eight treatments (1) Graston Technique 7) With the patient in the relaxed prone position, the Graston Technique was used on the trapezius, levator scapulae, latissimus dorsi, and rhomboid muscles. The instrument was held at a 45° angle for 120 to 180 seconds in a direction parallel to the muscle fibers.…”
Section: )Manual Therapymentioning
confidence: 99%
“…The Graton Technique and cervical Chuna manual therapy were done every two to three days for a total of eight treatments (1) Graston Technique 7) With the patient in the relaxed prone position, the Graston Technique was used on the trapezius, levator scapulae, latissimus dorsi, and rhomboid muscles. The instrument was held at a 45° angle for 120 to 180 seconds in a direction parallel to the muscle fibers.…”
Section: )Manual Therapymentioning
confidence: 99%
“…25 Their pre-test PSLR values were 90° which was measured at the patient's end feel. 25 Moon et al 26 reported evaluating hamstring ROM and its relation to nonspecific low back pain. They did not report average PSLR criteria, but one of their inclusion criteria were a PSLR of 70° or less.…”
Section: Hamstringmentioning
confidence: 99%
“…They did not report average PSLR criteria, but one of their inclusion criteria were a PSLR of 70° or less. 26 They did not have a requirement for physically active participants. 26 They treated the hamstring in a semi-flexed positioned between 30-60° while applying GT1.…”
Section: Hamstringmentioning
confidence: 99%
See 2 more Smart Citations